Scattering Analysis of Silver Nanoparticles for Solar Cell Applications using Integral Equations - Uysal, Ismail Enes; Bagci, Hakan; Ulku, Huseyin Arda; Gulseren, Oguz (IEEE, 2018)
Plasmonic nanoparticles (NPs) can be used to improve the efficiency of solar cells. Analysis of electromagnetic scattering from NPs is often carried out under the assumptions that they reside in air and have ideal shapes (sphere, cube, etc.) However, in a realistic setup, nanoparticles are fabricated on a substrate and their shape and size cannot be controlled precisely. In this work, a surface integral equation solver is used to accurately characterize the scattering from a realistic system, where silver hemispheres of varying sizes are fabricated on an indium tin-oxide substrate. Results obtained by the solver are compared to the experimental results obtained for a similar system.
International Applied Computational Electromagnetics Society Symposium (ACES) -- MAR 25-29, 2018 -- Denver, CO
Keywords: Electromagnetic scattering; plasmonics; solar cell; surface integral equations